(untitled) (Research, Society and Development, 2021)
The concern with sustainable development represents the possibility of guaranteeing socio-political changes that do not compromise the ecological and social systems that sustain life. In this context, a bibliographic and scientometric survey was carried out in terms of sustainable development, important tools to study and measure the progress of science in quantitative and qualitative analyzes. Productivity was ascertained through bibliometric assessments, using databases of access to science documents, “Elsevier Scopus” between the period: from 2009 to 2019, involving the keywords “Sustainable Development in Brazil”. The statistical analysis was expressed by the GraphPad Prism 6 program. In analyzing the data published in the “SCOPUS” database, it was possible to observe that the first work published with the concept “sustainable development in Brazil” was in 1982, and throughout the number of studies on this topic has been increasing steadily over the years, and today, 3,520 works are registered on this platform. Brazil stands out with the largest number of works in the last 10 years, totaling around 1976 works, where the ranking is led by “USP- Universidade de São Paulo”, a considerably important University in the country, with currently 324. Data like these they are promising to find out how is the productivity in a respective subject across the country.